The innovator's dilemma : when new technologies cause great firms to fail - Christensen, Clayton M. (Boston, Mass. : Harvard Business School Press, 1997)
This book takes the radical position that great companies can fail precisely because they do everything right. It demonstrates why outstanding companies that had their competitive antennae up, listened astutely to customers, and invested aggressively in new technologies still lost their market leadership when confronted with disruptive changes in technology and market structure. And it tells how to avoid a similar fate. Using the lessons of successes and failures of leading companies, The Innovator's Dilemma presents a set of rules for capitalizing on the phenomenon of disruptive innovation. These principles will help managers determine when it is right not to listen to customers, when to invest in developing lower-performance products that promise lower margins, and when to pursue small markets at the expense of seemingly larger and more lucrative ones.
How can great firms fail? Insights from the hard disk drive industry -- Value networks and the impetus to innovate -- Disruptive technological change in the mechanical excavator industry -- What goes up, can't go down -- Give responsibility for disruptive technologies to organizations whose customers need them -- Match the size of the organization to the size of the market -- Discovering new and emerging markets -- Performance provided, market demand, and the product life cycle -- Managing disruptive technological change: a case study -- The dilemmas of innovation: a summary.
Includes bibliographical references and index.
Keywords: Creative ability in business; Industrial management; Customer services; Success in business; Creative ability in business; Customer services; Industrial management